К функциональному значению червеобразного придатка человека в свете его филогенетического развития - Мельман, Е.П. (Вестник зоологии, 1969)
Using a great amount of literary data and material of the own observations, the author presented a morpho-functional analysis of the human appendix value in the light of its historical development. In spite of regressive changes of its primary form, the appendix possesses a strong nervous apparatus of a peculiar structure, contains a considerable accumulation of lymphoid tissue and well developed vascular net. It gives grounds to assume that the appendix, turned during the anthropogenesis into regressively changed organ, might preserve an accessory function not yet discovered, the presence of which inhibits its further reduction and conditions a high structure of this organ.